A descriptive analysis of selected community stakeholder opinions regarding potentially critical factors in school bond referenda success or failure in Kansas during the years 2004-2007 - Kraus, Brian W. (Kansas State University, 2009)
The purpose of this study was to analyze opinions of selected school district stakeholders regarding potentially critical factors in school bond referendum success and failure in Kansas during the years 2004-2007. Of the 72 eligible school districts, one district was randomly selected from each of six groups formed through a stratified random sampling process utilizing district enrollment (small, medium, large) and bond election result (successful, unsuccessful). Four purposefully selected respondents from each district participated in a mixed methods strategy of inquiry that included completing a 32-item written survey and participating in a personal interview. The survey served as the standardized data collection instrument. Survey data were used to augment and expand upon understanding of the bond referendum process gained from the personal interviews by examining respondents‟ perceptions of how important campaign strategies were, or would have been, in influencing election results. Frequency distributions were constructed in an attempt to identify relationships between variables identified as important to bond election success. Cross-tabulations and Pearson's chi-square were the statistical treatments chosen to further analyze the survey data. During the interviews, participants were asked a set of standard questions as well as questions unique to their role in the election process. The questions were designed to elicit in-depth responses about factors critical to the bond's success or failure and to gather useful advice for other districts preparing for a bond election. Interviews were used to discover new data, further develop existing data, and assist in organizing all data sources to construct a "story" describing bond election experiences in Kansas. The study findings indicate that unsuccessful districts utilize more campaign strategies and perceive them to be more important than successful districts, but that successful districts are more in tune with patrons. As each district is unique, it was found that strategies that were successful in one district might not be in another. Three factors found to be critical included: having unanimous school board support for the bond referendum, developing an on-going public relations strategy with patrons, and communicating the elements of a bond referendum to all patrons in simple, clear, and honest language.
Keywords: Bond elections; Bond referenda; Kansas; Education, Administration (0514); Education, Finance (0277)